Penggunaan Pita Fibre Reinforced Composite (FRC) Sebagai Pasak pada Gigi 21 dengan Bentuk Saluran Akar yang Lebar - Irma Widyasari; Irmaleny Satifil (Jurnal Material Kedokteran Gigi, 2013)
The primary purpose of a post is to retain a core and restoration on a tooth with extensive loss of coronal structure. However, preparation of a post space may increase the risk of the root canal fracture, especially in a large root canal. For reducing that, the new concepts was developed. the main idea was to build up a post that can be following anatomical form of the root canal, using minimal invasive preparation and made from the material which is modulus of elasticity closed to the dentinal. Its can be achieved by using custom fibre reinforced composite post. The aim of these case report was to inform the usage of custom fibre reinforced composite as root canal post on the endodontically treated tooth 21 with a large root canal. A 15 years old boy came to department of conservatif dentistry RSGM UNPAD to make a restoration for his endodontically treated tooth. The clinical examination revealed fracture horizontal on tooth 21 with less a half remaining coronal tooth tisue and discolorisation. Radiological examination showed radioopaque in whole of the root canal with increased width of the root canal to the coronal. Periapikal area was normally condition. The tooth was restored using custom fibre reinforced composite post and all porcelain crown as a final restoration. Custom FRC post was a good alternative for endodontically treated tooth with a large of the root canal that could be tailored to specific need, enabling preservation of tooth structure, and using minimal invasive preparation